Preparation and characterization of newly developed matrix using functional γ‐Fe2O3 nanoparticles for mass spectrometry in small molecules. (22nd July 2016) - Morimoto, Shota; Ishikawa, Tomoya; Hyodo, Kuminori; Yamazaki, Takahiro; Taira, Shu; Tsuneyama, Koichi; Ichiyanagi, Yuko
Abstract : Iron oxide magnetic nanoparticles were prepared by our original chemical wet method. These particles were functionalized by modification of amino groups and other molecules for biomedical application. The obtained particles were characterized by X‐ray diffraction, fourier transform infrared spectroscopy (FT‐IR), and magnetization measurements, and then local structures were analyzed using X‐ray absorption near edge structure (XANES). Functional nanoparticles were further developed as new matrices for mass spectrometry by modification of α ‐cyano‐4‐hydroxycinnamic acid (CHCA) so that small molecular weight could be detected, which was hard to observe the spectra so far. We have detected small molecular analytes such as colchicin (MW = 399.4 Da) and aspirin (MW = 180.1 Da) using our developed functional nanoparticles. We have successfully developed new matrices for analytes in the low mass range without impurities. Finally, we aimed to detect 2‐octynate methyl (2‐OAm, MW = 154.2 Da), which is one of the important candidates for the triggering of primary biliary cirrhosis (PBC), a liver disease almost exclusively found in women. Our functional magnetic nanoparitlces are expected to contribute to the biomedical field. Copyright © 2016 John Wiley & Sons, Ltd.